Detection of Pulpal Blood Flow In Vivo with Pulse Oximetry in Dogs - Riehl, Jessica; Hetzel, Scott J.; Snyder, Christopher J.; Soukup, Jason W. (Frontiers in Veterinary Science, 2016)
Objective: The aim of the present study was to investigate the ability of pulse oximetry to detect blood flow within the canine tooth of dogs. Materials and methods: Dogs aged 18-138 months presenting for oral treatment and meeting the inclusion criteria underwent pulse oximetry evaluation of at least one canine tooth. Oxygen saturation (SpO2) and pulse rate values were acquired from vital canine teeth of 38 clinical patients (representing 40 total teeth) with a hand-held pulse oximeter and compared to a control area. SpO2 values from the tooth and control area were recorded every 5 seconds for three 60-second intervals. The sensors were repositioned after each 60-second interval. Results: The vital teeth consistently recorded SpO2 values significantly lower than the control area. The mean vital tooth SpO2 was 85.9% (median = 87%; SD = 8.6) and the mean control area SpO2 was 97.7% (median = 98%; SD = 1.8). An age-related significant difference was noted in vital tooth SpO2 values. Conclusions: In conclusion, the present data supports the possible use of pulse oximetry to detect blood flow in canine teeth. However, there was no significant correlation between SpO2 values in the vital tooth and in the control areas. Additionally, the results were not definitive and validation of the modality with additional studies of non-vital canine teeth is needed before clinical use can be recommended.